ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN KEPULAUAN SULA - Sahdan, Rinto; Hormati, Asrudin; Irham, Jumiati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research aims to provide information to the public regarding the presentation of financial statements and the performance of local governments in realizing accountability. As well as knowing the performance of the local government of Sula Islands Regency by using the APBD financial ratio, especially the effectiveness ratio, efficiency ratio, independence ratio and harmony ratio, and growth ratio. The type of data used in this study is quantitative data. The data is documentation of the 2019-2021 APBD financial statements. The object of the research used is the Regional Government of Sula Islands Regency, namely the Regional Asset Management Revenue Office. The results of the research show that the analysis of financial ratios in the regional revenue and expenditure budget for the 2019-2022 fiscal year as measured through the effectiveness ratio of the 2019-2022 fiscal year is quite effective, the efficiency ratio of the 2019-2022 fiscal year is quite efficient, the independence ratio of the 2019-2012 fiscal year is very low, the compatibility ratio of the 2019-2022 fiscal year which explains that the results of the operating expenditure ratio are prioritized compared to the capital expenditure ratio, and the growth ratio of regional original income, revenue growth ratio, operating expenditure growth ratio, and capital expenditure growth, there is a fluctuating increase from 2019-2022.